The Ecstasy of Acceleration: the Problem of Capital in the Philosophy of Nick Land - Tuomas, Linartas (Problemos, 2022)
In this article, the anti-anthropocentric philosophy of Nick Land is discussed from the perspective of the concept of capital – capital becomes a philosophical problem. The origin of Land’s conception of capital as artificial intelligence alien to humanity is traced from the theory of libidinal materialism, the transcendental philosophy of Kant, and also from the historical and cultural background. The ideas of Deleuze and Guattari let Land think of capital as machinically and cybernetically accelerating techno-capital – Land’s intense relation to the process of acceleration is defined here as ecstasy. Also, the problematic interpretation of Deleuze and Guattari is noted, the processes of automatisation and autonomisation are considered, and Land’s teleological vision of technological singularity is criticised, especially from the point of the threats of the climate crisis. Here is shown that the philosophy of Land affectively follows the relevant and important tendencies of capitalism, but suffers from some inner contradictions and paradoxes, according to which we can reasonably doubt the philosopher’s ecstatic celebration of the abyss between capital and human subjectivity.